THE MANIFESTATION OF MAL’AKH AS THE ARCHETYPAL ANCIENT MYTHOLOGY IN DAN BROWN’S THE LOST SYMBOL - RIZKYANITA, RADITYA PUTRI BUDI (Jurnal Ilmiah Mahasiswa FIB, 2013)
Dan Brown’s The Lost Symbol is a controversial novel which adopts Freemasonry as the background of the story. Among the characters, Mal’akh is the interesting character to be analyzed because of his life phase which is coloured by myth, dream, and ancient knowledge. Related to this case, the theory of archetypes is used to analyze the object of the study. The archetypes is promoted by Carl G. Jung. The existence of archetypes can only be deduced indirectly by examining behavior, images, myths, religions, or dreams. The archetypes form a foundation of which each individual builds his own experience of life, colours them with his unique culture, personality and life events. This phase happened in the antagonist character named Mal’kah in Dan Brown The Lost Symbol. Related to this case, this study aims to show the manifestation of Mal’akh archetypes in the novel and to analyze the portrayal of Mal’akh’s archetypes as the representation of his images through his collective unconscious. This study uses qualitative approach particularly literary study to analyze phenomena related to the problem of the study.The finding of this study is that the images in Mal’akh’s early life while he was being Zachary Solomon and Andros Dareios were contained in Mal’akh collective unconscious. The motifs of Mal’akh which contains of the dream and knowledges also contained in Mal’akh collective unconscious. Those images are shaped Mal’akh unconscious mind  which manifest the Moloch image. Therefore, this study finally reveals the manifestation of Mal’akh as the archetypal ancient mythology.  It is suggested that the next researchers to do further study using the historical approach in order to broaden the critical analysis about the relationship between the archetypes and the ancients beliefs of the mythology.Keywords: Archetypes, Collective Unconscious, Dan Brown, Images, Mal’akh, Mythology , The Lost Symbol.